Danian foraminifera from Laxmi Basin, Northern Indian Ocean - Thena Thulasi; Dhananjai K Pandey; Raj K Singh; Nisha Nair; Kollaparambil Surendran Roshni (PANGAEA, 2023)
Deep-sea sediments from the International Ocean Discovery Program (IODP) Site U1457 (Laxmi basin, Northern Indian Ocean) at ~1100 meters below the seafloor (mbsf) of the Danian period (c. 66 – 61.6 Ma) are examined, which suggest that the foraminifera subsisted across the major geologic events. A foraminiferal census count (%) was performed under a microscope and species belonging to Bolivina, Bulimina, Cassidulina, Cibicidoides, Epistominella, and Oolina genera are found to be dominant in the region (Table 1). The species were grouped under relative abundance (benthic/planktic), habitual preference (infauna/epifauna), and shell composition (calcareous/agglutinated) with literature references (Table 2). Calcium carbonate (%) was calculated from inorganic carbon values analyzed in a coulometer (Table 2). Magnetic susceptibility of low frequency is measured through a Bartington MS2B sensor and the units of measurement are defined in Table 2. The assemblage of benthic foraminifera belonging to each morphogroup (Table 3). Oxic, Suboxic, Dysoxic benthic foraminifera and Oxygen content were calculated through transfer function from oxyphillic species (Table 4). Benthic foraminifera diversity pattern Fisher alpha calculated through PAST software. All the foraminifera representations are made in percentage and depth in the units of meters below the seafloor.